2021
DOI: 10.1177/13548166211014367
|View full text |Cite
|
Sign up to set email alerts
|

Board diversity and firm risk-taking in the tourism sector: Moderating effects of board independence, CEO duality, and free cash flows

Abstract: This study examines the effect of board diversity on risk-taking for tourism firms and analyzes the moderating effect of board independence, CEO duality, and free cash flows in this proposed relationship. Using a composite index of board diversity and a sample of tourism firms from the US hotel, restaurant, and airline industries, we find that greater board diversity leads to lower risk-taking, measured in standard deviation of return on assets. Moreover, we report that the risk-reduction effect of board diver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 78 publications
0
7
0
Order By: Relevance
“…Hence, the empirical evidence, contrary to our expectations, revealed that board independence-related policies do not currently serve the H&T sector's development. Although, in recent years, board independence has been accepted as an indispensable mechanism of board monitoring (Al-Najjar, 2014; Ozdemir et al. , 2022), board composition beyond maintaining a certain number of nonexecutive directors is essential.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the empirical evidence, contrary to our expectations, revealed that board independence-related policies do not currently serve the H&T sector's development. Although, in recent years, board independence has been accepted as an indispensable mechanism of board monitoring (Al-Najjar, 2014; Ozdemir et al. , 2022), board composition beyond maintaining a certain number of nonexecutive directors is essential.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, the empirical evidence, contrary to our expectations, revealed that board independence-related policies do not currently serve the H&T sector's development. Although, in recent years, board independence has been accepted as an indispensable mechanism of board monitoring (Al-Najjar, 2014;Ozdemir et al, 2022), board composition beyond maintaining a certain number of nonexecutive directors is essential. Moreover, based on the prior empirical evidence that board policies reinforce directors' abilities to ensure firms' financial stability (Gaganis et al, 2020), H&T firms are advised to review and revise their board-independence policies to recruit experienced directors in the sector, furnish them with the necessary autonomy and integrate them into corporate decision-making processes.…”
Section: The Moderating Role Of Indeppolicymentioning
confidence: 99%
“…First, from a theoretical perspective, this study contributes to the tourism and hospitality literature pertaining to corporate governance by revealing the positive relationship between board interlocks and corporate risk-taking, supporting the proponents of the resource dependence theory and the collusion theory. Although many hotel and tourism literatures have investigated the factors of corporate risk-taking, they mainly focus on the diversification of the board of directors (Lee and Thong, 2022; Ozdemir et al, 2021), CEO characteristics (Lee and Moon, 2016), CEO overconfidence (Seo and Sharma, 2018), and executive compensation incentives (Seo and Sharma, 2013). There are also some studies on chain directors, but these studies mainly examine the impact of board interlocks on the financial performance of tourism enterprises (Ooi et al, 2015; Song et al, 2021; Yousaf et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Corporate risk-taking (Risk i,t ). Common indicators of corporate risk-taking include the volatility of return on assets (Roa) (e.g., Boubakri et al, 2013;John et al, 2008;Ozdemir et al, 2021), stock return volatility (e.g., Bargeron et al ., 2010;Coles et al, 2006), debt ratio (e.g., Faccio et al, 2011Faccio et al, , 2016, and the possibility of firm survival (e.g., Faccio et al, 2016). Due to the special institutional and policy environment in China, the living conditions of listed companies in China can be affected by government policies.…”
Section: Variables Measurementioning
confidence: 99%
“…The association between risk and the aforementioned factors has been largely investigated by previous research, leading to mixed evidence (Di Pietra et al, 2008;Ozdemir et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%